2015
DOI: 10.1002/elps.201400524
|View full text |Cite
|
Sign up to set email alerts
|

Differential microfluidic sensor on printed circuit board for biological cells analysis

Abstract: Coulter principal based resistive pulse sensor has been demonstrated as an important platform in biological cell detection and enumeration since several decades ago. Recently, the miniaturized micro-Coulter counter has attracted much attention due to its advantages in point of care diagnostics for on chip detection and enumeration of rare cells, such as circulating tumor cells. In this paper, we present a microfluidic cytometer with differential amplifier based on Coulter principle on a SU-8 coated printed cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Nevertheless, it has been demonstrated that by replacing the meander lines with artificial lines, sensitivity optimization can be made compatible with moderate or even small sizes [12,60]. Many differential sensors based on resonator-loaded lines (the interest in this work) have been reported, including microfluidic sensors for liquid characterization [61][62][63][64][65][66][67]. In some realizations, the output variable is the cross-mode transmission coefficient [62][63][64][65][66][67], proportional to the difference between the transmission coefficients of both sensing lines, provided such lines are uncoupled.…”
Section: Classification Of Planar Microwave Resonant Sensorsmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that by replacing the meander lines with artificial lines, sensitivity optimization can be made compatible with moderate or even small sizes [12,60]. Many differential sensors based on resonator-loaded lines (the interest in this work) have been reported, including microfluidic sensors for liquid characterization [61][62][63][64][65][66][67]. In some realizations, the output variable is the cross-mode transmission coefficient [62][63][64][65][66][67], proportional to the difference between the transmission coefficients of both sensing lines, provided such lines are uncoupled.…”
Section: Classification Of Planar Microwave Resonant Sensorsmentioning
confidence: 99%
“…But the early traditional cell experiments used only standard benchtop instruments, making cell analysis only allowed to be performed in professional laboratories [33][34][35][36]. Recently, many researchers use PCB-based resistance sensors or capacitive sensors to build a Lab-on-PCB platform to count cells or detect cell viability for disease diagnosis and drug toxicity detection in a low-cost and mini-size way [37][38][39][40][41][42][43].…”
Section: Cell Analysismentioning
confidence: 99%
“…100 Disposable PDMS-PCB chips were also reported for electrophoretic separation and amperometric DNA detection 101 or low cost detection and enumeration of circulating tumor cells in a microfluidic impedance cytometer. 102,103 In addition, highly integrated microfluidic components and LoC devices have been developed on PCB substrates for on-chip sample preparation, DNA amplification and detection, by integrating multiple embedded heating and sensing elements together with electrical circuitries on a PCB with a polymeric cover where the microfluidic network (mixers, valves, pumps, etc.) was micromilled.…”
Section: Technology Overview and Demonstrated Prototypesmentioning
confidence: 99%